Cepec Herbarium database update proposal - Lopes, Marcos Reis; Silva, Vânia Cordeiro; Araujo, Quintino Reis; Novais, Renato Nunes da Silva (MAGISTRA, 2019)
Abstract: Herbarium databases offer information about plant taxonomy, ecology, phytotherapeutics, and ethnobotanicals, among other subjects that focus on regional and international flora. These databases require a high degree of reliability. This work consists of an applied and detailed study on two databases, with different architectures, of the Cocoa Research Center [CEPEC, acronym in Portuguese] Herbarium, in Executive Commission of the Cacao Farming Plan [CEPLAC], Brazil, which had to be remodeled, standardized and merged into a single database, and a proposal for a dedicated system to add, delete and edit existing data. This document is intended for botanists, as well as practitioners of related fields and who have in botany an important source of information. Results reflect the importance of each software according to analysis, definition of requirements and software development. A new database system is proposed for immediate use by the staff and technicians of CEPEC’s Herbarium. Key words: Systematization of botanical information, Exsicata, Brazilian Flora.